2019
DOI: 10.3390/molecules24030523
|View full text |Cite
|
Sign up to set email alerts
|

Skin Electrical Resistance Measurement of Oxygen-Containing Terpenes as Penetration Enhancers: Role of Stratum Corneum Lipids

Abstract: The measurement of skin electrical resistance (SER) has drawn a great deal of attention for the rapid screening of transdermal penetration enhancers (PEs). However, the mechanisms underlying the SER measurement are still unclear. This study was to investigate the effects and mechanisms of seven oxygen-containing terpenes on the SER kinetics. Stratum corneum (SC) lipids were proved to play a key role in SER measurement. Then, the factors affecting the SER measurement were optimized. By the determination of SER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Zhu et al evaluated seven oxygen-containing terpenes (1,8-cineole, citral, geraniol, linalool, menthol, terpinen-4-ol, and α-terpineol) at a concentration of 5%; both cyclic and linear forms were evaluated using the method of measuring skin electrical resistance (SER), the changes of which reflect the degree of skin integrity after application of compounds considered to be API permeation enhancers. , Cyclic terpenes (1,8-cineole, terpinen-4-ol, menthol, and α-terpineol) were shown to reduce SER values and impair the skin’s barrier function to a greater extent than linear terpenes (linalool, geraniol, and citral). Molecular computer simulations indicated that the SER values for cyclic terpenes were associated with the formation of stronger hydrogen bonds with the polar head of SC ceramides creating a pathway for hydrophilic API penetration (LogP > 3), as well as a pathway for water to escape through the epidermis. , …”
Section: Natural Compounds With the Penetration-enhancing Potential O...mentioning
confidence: 99%
See 2 more Smart Citations
“…Zhu et al evaluated seven oxygen-containing terpenes (1,8-cineole, citral, geraniol, linalool, menthol, terpinen-4-ol, and α-terpineol) at a concentration of 5%; both cyclic and linear forms were evaluated using the method of measuring skin electrical resistance (SER), the changes of which reflect the degree of skin integrity after application of compounds considered to be API permeation enhancers. , Cyclic terpenes (1,8-cineole, terpinen-4-ol, menthol, and α-terpineol) were shown to reduce SER values and impair the skin’s barrier function to a greater extent than linear terpenes (linalool, geraniol, and citral). Molecular computer simulations indicated that the SER values for cyclic terpenes were associated with the formation of stronger hydrogen bonds with the polar head of SC ceramides creating a pathway for hydrophilic API penetration (LogP > 3), as well as a pathway for water to escape through the epidermis. , …”
Section: Natural Compounds With the Penetration-enhancing Potential O...mentioning
confidence: 99%
“…62 FTIR (Fourier-transform infrared spectroscopy) results confirmed that limonene interacts with the alkyl chain region of SC lipids causing an increase in fluidization, as it relaxes the lamellar organization of the lipids. 170 Zhu et al 171 evaluated seven oxygen-containing terpenes (1,8cineole, citral, geraniol, linalool, menthol, terpinen-4-ol, and αterpineol) at a concentration of 5%; both cyclic and linear forms were evaluated using the method of measuring skin electrical resistance (SER), the changes of which reflect the degree of skin integrity after application of compounds considered to be API permeation enhancers. 172,173 Cyclic terpenes (1,8-cineole, terpinen-4-ol, menthol, and α-terpineol) were shown to reduce SER values and impair the skin's barrier function to a greater extent than linear terpenes (linalool, geraniol, and citral).…”
Section: Natural Compounds With the Penetration-enhancing Potential O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also evaluated the cytotoxicity of the EOs distilled from plants not belonging to the genus Lippia and from the terpenes studied here on the HaCaT cell line, with CC 50 values ranging between 33.93 and 1701.97 μg/mL [ 42 , 43 , 44 ]. The CC 50 values obtained in our study with the Lippia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Histology, 6 small-angle X-ray scattering (SAXS), 7,8 and fluorescence spectroscopy 9 are often destructive or are performed under nonphysiological conditions. To overcome these drawbacks, a variety of label-free optical techniques have been used to measure the components and structure of SC, including multiphoton imaging, 10,11 Fourier transform infrared (FT-IR) spectroscopy, 12,13 and Raman spectroscopy (RS). 7,14−20 Confocal Raman spectroscopy (CRS) is widely accepted as a non-invasive, label-free, accurate, and fast technique for chemical composition determination, 14,15 biological imaging, 18,19 and SC studies.…”
Section: Introductionmentioning
confidence: 99%